HUBUNGAN PERSONAL HYGIENE TERHADAP KEJADIAN PITYRIASIS VERSICOLOR DI PANTI ASUHAN PUTERI AISYIYAH KOTA MEDAN - TAMARA YUSANDA PUTRI; HERVINA . (LP2MTBM MAKARIOZ, 2020)
Personal hygiene is an activity in which done by someone directly and indirectly to keep her health to prevent the risk of aninfectious disease. Personal hygiene on the skin is the primary mechanism for reducing contact and transmission ofinfection, fungal infection Pityriasis versicolor. The amount of activity that sweats and the lack of hygiene personal cancertainly be a trigger factor for infected Malassezia furfur. To determine the relationship between personal hygiene with theoccurrence of Pityriasis versicolor among students at the Aisyiyah Orphanage House Medan. This study was an descriptiveanalitic using cross sectional design. The results were analyzed using Chi-Square. The population in this research were 65students. The sampling result is done by total sampling method. Data collection uses primary data in the from aquestionnaire consisting of 16 questions, then all of the sample will get wood lamp examination. The proportion of Pityriasisversicolor incidence was 40 respondents (61.5%) with the most teenager aged 14 years. Personal hygiene among childrenbased on the questionnaire was in the poor category that is 43 (66.2%) respondents . Statistical test showed that the p valuewas 0.0001 (p<0.05) and it means that personal hygiene affected the incidence of Pityriasis versicolor. There was asignificant correlation between personal hygiene to the incidence of Pityriasis versicolor in the Orphanage Aisyiyah Medan.